Blended SoS: A New Evolutionary Approach for Complex Information Systems - Lana, Cristiane Aparecida; Silva, Samira; Affonso, Frank José; Oliveira, Johnatan Alves de; Nakagawa, Elisa Yumi; Vilella, Maria Lúcia Bento (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: This study investigates complex socio-technical Systems-of-Systems (SoS), focusing on environments where operational technology (OT) and information technology (IT) converge, such as in the domains of Agro 4.0 and eHealth. These domains are at the forefront of digital transformation, requiring innovative approaches to integrate distinct and emerging technologies effectively. Scientific and/or Practical Problem: Existing SoS classifications are insufficient to capture the hybrid and evolutionary nature of real-world systems. Newly designed, legacy, and proprietary systems often coexist and must interoperate within the same ecosystem, creating gaps in understanding emergent behaviors, stakeholder interactions, and technical interoperability. This represents a significant challenge for building resilient and adaptable systems. Proposed Solution and/or Analysis: We introduce the concept of Blended SoS, a novel category of SoS characterized by limited central control, heterogeneous constituents, and adaptive, mission-driven behaviors. We organized this concept within a framework that integrates principles from mission engineering, SoS engineering, and information systems (IS) to guide the design, operation, and evolution of complex systems across various domains. Related IS Theory: The research adopts principles from hermeneutics and grounded theory, providing an interpretive understanding and enabling the emergence of substantial theory within the IS field. Research Method: Qualitative data from interviews and surveys were systematically coded and synthesized into a theoretical framework, validated against existing literature. Summary of Results: Findings highlight the importance of adaptive architectures, stakeholder-centric governance, and technical interoperability to ensure resilience, continuous availability, and alignment with missions. Contributions and Impact to IS area: This study formalizes the Blended SoS category, providing a framework for managing adaptive, multi-domain systems. This framework advances sociotechnical understanding of SoS, guides interoperability and governance, and supports decision-making in complex, dynamic IS environments.